2017
DOI: 10.3329/ajmbr.v3i1.32044
|View full text |Cite
|
Sign up to set email alerts
|

Performance of some growth promoters on hybrid walking catfish (Clarias batrachus × Clarias gariepinus)

Abstract: Abstract:A study was conducted to determine the efficacy of three most commonly used growth promoters from different pharmaceutical companies on growth performance of hybrid walking catfish (Clarias batrachus × Clarias gariepinus). The experiment was done in the wet laboratory of the Department of Aquaculture, BAU, Mymensingh, with a total of 10 aquaria and 160 fish having mean initial weight of 6.3 ± 0.48 g. The three growth promoters, "Charger gel" from Fishtech (BD) Ltd., "Growth gel" from Advance Agrotech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
4
0
0
Order By: Relevance
“…Hossain et al (2003) found that ammonia (NH4) in different treatments is varied from 0.004 to 0.077 mg/L that was insistent to the findings of present study. Similar study were conducted by Samad et al (2016); Islam et al (2017); ; Shabuj et al (2016); Rahman et al (2015); Ali et al (2016b); Rahman et al (2016) and Anka et al (2016); their results were also similar. Nitrite can be associated with ammonia concentration in the water body.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Hossain et al (2003) found that ammonia (NH4) in different treatments is varied from 0.004 to 0.077 mg/L that was insistent to the findings of present study. Similar study were conducted by Samad et al (2016); Islam et al (2017); ; Shabuj et al (2016); Rahman et al (2015); Ali et al (2016b); Rahman et al (2016) and Anka et al (2016); their results were also similar. Nitrite can be associated with ammonia concentration in the water body.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, nitrite concentration ranged from 0.01 mg/L to 0.03 mg/I, with the mean values of 0.013±0.01 mg/L, 0.01510.01 mg/L and 0.02710.01 mg/L, which was more or less similar to the findings of (Begum and Vijayaraghavan, 1999) who found that nitrite-nitrogen varied from 0.008 to 0.026 mg/L and 0 to 0.029 mg/L, respectively. Similar study were conducted by Samad et al (2016); Islam et al (2017); Rahman et al (2017); Rahman et al (2016) and Anka et al (2016); their results were also similar. In the present study, phosphate ranged from 0.6 to 1 mg/L which was more or less similar to the findings of Rahman (2003) who reported that PO 4 -P concentration varied from 0.78 to 2.5 mg/L in different treatments.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…To attain this, Labeo rohita, a commercially important cultured fish was selected as the experimental fish due its large consumer demand along with three different groups of growth promoters, depending on their active main ingredients (beta glucans, vitamin and mineral premix, dietary multienzyme) and mode of action (immunomodulation, micronutrient supplementation, enhancing digestion) and how they influence feed efficiency. The use of growth promoters on several species of fish like Clarias batrachus [10]. Oreochromis niloticus [11].…”
Section: Introductionmentioning
confidence: 99%